Proza Iwana Szmielowa w kontekście duchowego paradygmatu rosyjskiej literatury klasycznej (w perspektywie wybranych aspektów rosyjskich badań szmieloznawczych ostatnich lat) - Horczak, Dorota (Studia Rossica Posnaniensia, 2012)
This article, based on some contemporary Russian literary research studies, contains a reflection on Ivan Shmelov’s prose in the context of the spiritual paradigm of Russian classical literature. Typical Shmelov motifs, such as the “Holy Rus”, a monastery as a symbol of an Orthodox center, the spiritual life of heroes, the individual and national internal way towards a new religious Renaissance – are developed in the manner of “spiritual realism”. They are also linked with the religious themes and aspects of the prose of Russian emigrant writers as well as with prerevolutionary pieces of literature, including texts from the time of old Russian literature.